The mediating role of thyroid-related hormones between thyroid dysfunction diseases and osteoporosis: a mediation mendelian randomization study - Ruikang Liu; Weiming Fan; Jiaming Hu; Ke Xu; Zhijian Huang; Yang Liu; Chiyun Sun (Scientific Reports)
Abstract The links between Thyroid dysfunction diseases (TDFDs) and osteoporosis (OP) has received widespread attention, but the causal relationships and mediating factors have not been systematically studied. We used two-sample Mendelian randomization (MR) analysis to elucidate the causal relationship between TDFDs and OP. Moreover, we performed mediation MR analyses to explore the role of thyroid-related hormones and OP risk factors in the association between TDFDs and OP. Two sample MR analyses showed that hyperthyroidism increased OP (OR = 1.080, 95% CI 1.026 to 1.137; P = 0.0032) risk. Hypothyroidism increases OP (OR = 1.183, 95% CI 1.125 to 1.244; P < 0.0001) risk. Furthermore, mediation analysis revealed that TSH mediated 5.314% of the relationship between hypothyroidism and OP. In contrast, FT4 mediated 9.670% of the relationship between hyperthyroidism and OP. In European populations, TDFDs may increase OP risk. TSH mediates in the causal association between hypothyroidism and OP, and similarly, FT4 mediates in the causal link between hyperthyroidism and OP. Our findings underscore the significance of improving integrative care for individuals with TDFDs to mitigate the risk of OP. It is essential to maintain stable levels of thyroid hormones and closely monitor bone health to effectively mitigate and prevent OP.